The role of sex segregation in the gender wage gap among university graduates in Germany - Juliane Ransmayr; Doris Weichselbaumer (Journal of Economics and Statistics, 2024)
In this paper we examine the gender wage gap among university graduates in Germany from 1997 to 2013 based on the DZHW (the German Centre for Higher Education Research and Science Studies) Absolventenpanel. We focus in particular on the effect of female presence in a subject or occupation on wage inequality. Earlier research has shown not only that female-dominated university subjects or occupations pay less, but also that men face a higher wage penalty than women when they graduated in a female-dominated subject and experience a lower penalty for working in a female-dominated occupation. For the five waves considered, we confirm the very strong negative association between female presence in a subject or occupation and wages. However, no consistent pattern emerges with regard to whether men's or women's wages suffer larger penalties. There is also no time trend observable with regard to the wage penalty that is associated with female-dominated fields. We further show that significant gender wage gaps exist within fields of studies, especially in male-dominated fields like engineering and natural science.
Keywords: J16; J3; J7; 330; gender wage gap; sex segregation; university graduates